Significant Design Values for Outdoor Learning Environment in Higher Learning Institutions - Abdullah, Fadzidah; Yaman, Maheran; Sanusi, Aliyah Nur Zafirah; Asif, Nayeem; Salim, Farha (Journal of Architecture, Planning and Construction Management, 2021)
Higher learning institution is the place where knowledge of many different disciplines of educational programs is concentrated and disseminated to students. In tertiary education system, beside gaining knowledge, students are engaging in diverse social, economic, and cultural activities. In the contemporary formal learning system at higher learning institution, students have minimal exposure to outdoor learning activities because they are using exam oriented educational programs. In addition, the utilization of outdoor spaces for learning is perceived as giving discomfort for learning, because there is not enough provision of learning tools and facilities. This study has the objective to identify the most recent characters of outdoor learning setting that are significant for effective higher educational programs. Review of recent scholars’ works is conducted to develop a design framework for outdoor learning in the higher learning institution and later, survey questionnaire is conducted to validate the significance of identified design characters. This study would highlight the characters of outdoor learning spaces, as parts of the significant design values in developing and improving students’ learning experience at tertiary level. The information generated from this study may benefits the policy makers, the higher education authorities, designers, academicians, and future students, with a greater understanding on how to design and utilize successful outdoor learning space at higher learning institutions.